Identification of small for gestational age by population-based and customized growth charts in newborns of obese and normal-weight primiparous women. (1st November 2016) - Lauring, Julianne R.; Gupta, Megha; Kunselman, Allen R.; Repke, John T.; Pauli, Jaimey M.
Abstract: Objective: Our hypothesis was that newborns of obese mothers would be more likely to be classified as small for gestational age (SGA) by their customized growth curves than by the standard growth curves when compared to newborns of normal-weight mothers. Methods: This is a retrospective cohort of primiparous patients delivering between 1 July 2008 and 30 June 2012. Normal-weight was defined as BMI ≤25 kg/m 2 and obese as BMI ≥ 30 kg/m 2 . Infant birth-weight was characterized as SGA or non-SGA from the Lubchenco curve, the Fenton Preterm Growth Chart, and the customized growth curve. Results: Infants were more likely to be classified as SGA on the customized curve compared with Lubchenco curve. Odds ratio was 2.8 (CI: 1.7–4.4; p = 0.001) for obese women and was 2.9 (CI: 1.7–5.1; p < 0.001) for normal-weight women. Infants were also more likely to be classified as SGA based on the customized curve compared with the Fenton Preterm Growth Curve. The odds ratio was 2.3 (CI: 1.4–3.8; p = 0.001) for obese women and was 1.5 (CI: 1.01–2.33; p = 0.04) for normal-weight women. Conclusions: Population-based curves may mask SGA in obese women. Our study demonstrates that customized growth curves identify more SGA than population-based growth curves in obese and normal-weight women.